Pengembangan Typing Game sebagai Sarana Melatih Meningkatkan Kecepatan Mengetik Berbasis Desktop - Muhammad Arsa Adilla; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research enacts the fast typing via gaming platform. There are four menu options; "Start": will commence the session, "How to Play": is the instructional gameplay guide, "Credits": lists the sources of assets that were used to create the game, "Exit": closes the application. Synopsis: Player will control a spaceship that destroys incoming asteroids. Typing words correctly, will preserve the ship.The Game Development Life Cycle (GDLC) method, was used to produce the game. The GDLC method consists of an initiation stage regarding early game concept, pre-production staging that examines the game application creation process. This game was developed using Unity2D software. Two types of tests were conducted. A Functionality Test, showed the game operating at an optimal level. A User Experience Test outcomes demonstrated, improved user typing speed. Result of this research is through Windows operation based application in .EXE file format.